Are Pediatric Manual Resuscitators Only Fit for Pediatric Use? A Comparison of Ventilation Volumes in a Moving Ambulance. (19th May 2023) - Sun, Gregory; Wojcik, Susan; Noce, Jennifer; Cochran-Caggiano, Nicholas; DeSantis, Tracie; Friedman, Steven; Cooney, Derek R.; Knutsen, Chrisitan
Abstract: Background: The manual resuscitator device is the most common method of ventilating patients with respiratory failure, either with a facemask, or with an advanced airway such as an endotracheal tube (ETT). Barotrauma and gastric inflation from excessive ventilation volumes or pressure are concerning complications. Ventilating adult patients with pediatric manual resuscitator may provide more lung-protective tidal volumes based on stationary patient simulations. However, use of a pediatric manual resuscitator in mobile simulations contradictorily generates inadequate tidal volumes. Methods: Sixty-two emergency medical services (EMS) clinicians in a moving ambulance ventilated a manikin using pediatric and adult manual resuscitators in conjunction with oral-pharyngeal airway, i-gel, King LTS-D, or an endotracheal tube. Results: Oral-pharyngeal airway data were discarded due to EMS clinician inability to produce measurable tidal volumes. Mean ventilation volumes using the pediatric manual resuscitator were inadequate compared to those with the adult manual resuscitator on all other airway devices. In addition, i-gel, King LTS-D, and endotracheal tube volumes were statistically comparable. Paramedics ventilated larger volumes than emergency medical technicians. Conclusions: Using a pediatric manual resuscitator on adult patients is not supported by our findings.